PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN STAD DENGAN MEDIA REALIA SISWA KELAS 4 SDN DADAPAYAM 01 - Ika Puspita Putri; Wasitohadi ,; Theresia Sri Rahayu (Jurnal Karya Pendidikan Matematika, 2019)
This research is a Classroom Action Research consisting of 2 cycles. The subjects of this study were all 4th grade students of SDN Dadapayam 01. Techniques for collecting data were formative tests and observation sheets. The results showed that using Student Teams Achievement Division (STAD) type with Media Realia can improve students mathematics learning outcomes. This can be seen when the pre-cycle students who completed the KKM were 6 students (40%), the first cycle increased which was around 9 students who met the KKM (60%) and in the second cycle there was a significant increase of 13 students (87%) students has reached KKM. So it can be concluded that the use of STAD model with Media Realia in Mathematics learning can improve learning outcomes. Teachers can use the STAD model on other glasses and students are expected to be more active and responsible for group discussion activities.